APPLICATION OF SCANNING ELECTRON MICROSCOPE TO ANALYSE CURCUMA LONGA PRIMARY TINCTURE AND HIGHER DILUTION - DR. MONIMALA PRAMANICK; DR. MAYANK ROY; DR. SURAJ BHADORIA (The Bioscan, 2025)
Background: Curcuma Longa,the turmeric is used as a medicine and antiseptic from the ancient time. Here we have tried to recognise curcuma longa in higher dilutions as a nano particle by SEM. Whereas it is neglected and beyond the knowledge of new researcher that in higher dilutions also, we can identify the nano particles of Curcuma Longa. For these we can go through FTIR, SEM , UV Spectroscopy etc. Objective: Through this research work synthesizing the Nanoparticles of Curcuma Longa Primary tincture and 2x potency with the help of Chemical method, Dynamisation is done. Method: Potassium ferricyanide used as a Biocatalyst. The t Primary incture and 2x is analysed by Scanning electron microscope. Result: The Nano particles of Curcuma Longa is identified in Scanning electron Microscope, Primary Tincture as well as 2x. Conclusion: We can conclude that in higher dilution we can identify the particles of Curcuma Longa.